2020
DOI: 10.1016/j.ejso.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative administration of non-steroidal anti-inflammatory drugs in colorectal cancer surgery does not increase anastomotic leak rate; A systematic review and meta-analysis

Abstract: Background: Evidence on the effect of non-steroidal anti-inflammatory drugs (NSAIDs) on anastomotic leak (AL) rate after colorectal surgery is conflicting. Effects of NSAIDs might depend on the underlying disease. This meta-analysis aimed to review the effect of NSAIDs on AL rate in a homogeneous colorectal cancer patient population. Methods: A systematic literature search using MEDLINE and EMBASE database was performed for studies with AL as primary outcome comparing NSAID use in the early postoperative phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…NSAIDs are equally useful in postoperative analgesia. However, the concern of an increased risk of an anastomotic leak remains, but recent literature and meta-analysis remain inconclusive [ 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…NSAIDs are equally useful in postoperative analgesia. However, the concern of an increased risk of an anastomotic leak remains, but recent literature and meta-analysis remain inconclusive [ 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous meta-analysis has examined the effect of NSAIDs on the healing of anastomoses after colorectal surgery ( 26 , 27 ). Modasi et al discovered that post-colorectal surgery NSAID administration increases anastomotic leak rate, while Arron et al discovered that post-colorectal cancer surgery NSAID administration does not increase anastomotic leak rate ( 26 , 28 ). There is still controversy over whether post-colorectal surgery NSAID administration will increase the anastomotic leak rate, and more clinical studies are needed to verify it.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy over whether post-colorectal surgery NSAID administration will increase the anastomotic leak rate, and more clinical studies are needed to verify it. Arron et al also found that neither non-selective NSAID use nor COX-2 selective NSAID use caused an increased anastomotic leak rate ( 28 ). Besides, Huang et al and Modasi et al discovered that ketorolac was not associated with an increase in leak rate; however, their meta-analyses only included 2–3 studies on ketorolac ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several guidelines have identified non-steroidal anti-inflammatory drugs (NSAIDs) as the key opioid-sparing component of multimodal analgesia [3,4] and there is evidence that their use reduces the time to flatus and stool [55]. However, their use remains controversial due to a possible association with anastomotic leakage [56][57][58][59]. Non-selective NSAIDs are likely to be higher risk than selective NSAIDs [58].…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%